1990
DOI: 10.3109/17453679008993513
|View full text |Cite
|
Sign up to set email alerts
|

Distraction effects on the physis in rabbits

Abstract: Gradual physeal distraction by external fixation was performed on the distal femur in 19 growing rabbits. The rate of distraction was 0.5-1 mm once daily. Distraction was continued for 1-21 days until killing. Lengthening of the femur and latitudinal growth of the distraction area were measured in radiographs. Morphologic changes in the physes were studied in histologic preparations. The length gained by distraction was maximally 5 mm. Latitudinal overgrowth was noted in specimens distracted for more than 13 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…De Pablos also noted that the lower the rate of distraction employed, the greater was the short-and long-term viability of the physis. Other reports have confirmed de Pablos' observations [1,2,5,19]. In addition, these studies have shown that the apparent thickening of the physis with distraction is caused by a decrease in the enchondral ossification rate with an ensuing accumulation and disorganization of hypertrophic chondrocytes.…”
Section: Discussionsupporting
confidence: 75%
“…De Pablos also noted that the lower the rate of distraction employed, the greater was the short-and long-term viability of the physis. Other reports have confirmed de Pablos' observations [1,2,5,19]. In addition, these studies have shown that the apparent thickening of the physis with distraction is caused by a decrease in the enchondral ossification rate with an ensuing accumulation and disorganization of hypertrophic chondrocytes.…”
Section: Discussionsupporting
confidence: 75%
“…Physeal distraction leads to hyperplasia of the proliferative and hypertrophic zones , Connolly et al 1986, Alberty et al 1990, Kenwright et al 1990). This hyperplasia occurs whether or not physeal separation occurs Noble 1978, Alberty et al 1990).…”
Section: Effects Of Compressionmentioning
confidence: 99%
“…Transient hyperplasia of the physis is common during physeal distraction , De Bastiani et al 1986, Elmer et al 1989, Alberty et al 1990, De Pablos and Canadell 1990. Fracture-separation of the growth plate occurs in rabbits, if the distraction force exceeds 2 kp , Nakamura et al 1991.…”
mentioning
confidence: 99%
“…The cause of growth inhibition and physeal damage after limb lengthening has been analyzed in animal models (Pennecot et al 1983, Alberty et al 1990, Albanese et al 1996). These studies demonstrated that continuous compressive forces on the physis result in either temporary or permanent cessation of growth (the Heuter-Volkmann principle).…”
Section: Discussionmentioning
confidence: 99%